Pengembangan Bahan Ajar Teks Anekdot Berbantuan Canva di SMK Negeri 1 Percut Sei Tuan - Sianturi, Juwita; Zai, Ayu; Rahayu, Ramadhani Sri; Fauziah, Zahira; Hulu, Raffina Austin; Aminanda, Marsya; Azizah, Nurul (Journal of Education Religion Humanities and Multidiciplinary, 2025)
This study aims to develop Canva-based anecdotal text teaching materials to increase the interest, understanding, and self-confidence of students at SMK Negeri 1 Percut Sei Tuan. Previously used conventional teaching materials were deemed uninteresting and inappropriate for the visual learning characteristics of vocational school students. The study used a Research and Development (RD) approach with the 4D model (Define, Design, Develop, Disseminate), employing interviews, observations, and questionnaires with teachers and students. The results showed that existing teaching materials were ineffective in supporting anecdotal text practice, resulting in students having difficulty expressing ideas creatively. Teaching materials developed through Canva — in the form of comic strips, interactive presentations, and videos — have been shown to increase student motivation, engagement, and self-confidence. Therefore, Canva-assisted media effectively improves the quality of anecdotal text learning and supports students' creative skills in line with the demands of 21st-century learning.